Tomotherapy radiosurgery for arteriovenous malformations: current possibilities and future options with helical tomotherapy dynamic jaws? - Krause, Sonja; Beck, Sebastian; Schramm, Oliver; Schubert, Kai; Hauswald, Henrik; Zabel-du Bois, Angelika; Herfarth, Klaus; Debus, Jürgen; Sterzing, Florian (Technology in cancer research & treatment, 2013)
This planning study was performed to compare stereotactic linac based radiosurgery of Arteriovenous Malformations (AVM) with current Helical Tomotherapy (HT) and future HT techniques. For 10 patients with AVM, dose distributions and treatment times of “regular” HT delivery (Reg 2.5/1/0.6 cm field width), Running-Start-Stop Treatment (RSS 5/2.5 cm), Axial Mode (Axial 5 cm) and Dynamic Jaw/Dynamic Couch delivery with a maximum field width of 5 cm (DJDC 5) were analysed and compared to linac-based stereotactic radiosurgery. Axial produced the fastest treatment (Axial 4:47 min vs. Linac 32:42 min) at the cost of large brain exposure (V10% 289 ml). Except for Reg 0.6, all other HT techniques achieved significantly shorter treatment times than linac-based treatment (e.g. Reg 1, 19:42 min, DJDC 6:30 min). However, high-dose brain exposure (V60%) was higher in all HT plans (e.g. Reg 0.6, 10 ml, Linac 9 ml), and only Reg 0.6 showed better low-dose exposure (V10% of 167 ml vs. 199 ml, not significant). Neither current nor future HT modes in their current version outperformed linac-based stereotactic radiosurgery. However, AVM with special geometry might still benefit from HT.
Gesehen am 28.10.2021